People's Republic of China : Financial Sector Assessment Program- Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents an assessment of the level of observance of the Basel Core Principles for Effective Banking Supervision (BCPs) in China. The China Banking Regulatory Commission (CBRC) has maintained its momentum in regulation and supervision in the face of exceptional growth in scale and increasing complexity of the banking system. The CBRC has also achieved a high degree of compliance with the BCPs. However, several dimensions of credit risk, including treatment of problem assets, concentration risk and related party exposures have aspects in which they lag international best practices and standards. Failure to resolve these issues may hamper the CBRC in its task of assessing the nature and scale of credit risk in the system and within individual institutions.